2023
DOI: 10.1017/s0272263122000584
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in self-regulated learning profiles of Chinese EFL readers: A sequential explanatory mixed-methods study

Abstract: This study explored the latent profiles of self-regulated learning (SRL) strategies (cognitive, metacognitive, and motivational regulation) endorsed by Chinese English-as-a-foreign-language (EFL) readers in a high-stakes testing environment, and also their associations with individual factors (gender, grade, reading proficiency, and motivational beliefs). With a sequential explanatory mixed-methods design, students in grades 11 and 12 (n = 1,113) completed a reading comprehension test and a questionnaire regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…In primary school a study involving 291 students from Hong Kong found sex differences in the use of SRL strategies, specifically in the strategies of planning, acting on feedback, and self-initiation in academic writing contexts in favor of girls ( Bai et al, 2020 ). In secondary schools, similar results have also been found, for example, research with students from Turkey ( Karademir and Deveci, 2019 ) and other studies with students from China in both face-to-face ( Chen et al, 2023 ) and online learning contexts ( Liu et al, 2021 ) found that self-regulation skills differ significantly as a function of sex in favor of female students. In Higher Education, these differences are also confirmed, for example, a study of 153 undergraduate students of Biological Education in Indonesia showed that female students are more self-regulated, specifically in goal setting, task strategies, time management, and self-evaluation ( Anazifa et al, 2023 ); on the other hand, in a study in 700 undergraduate students of the Faculty of Foreign Languages in Turkey, similar results are revealed showing that female students are more self-regulated in comparison to male students ( Adıgüzel and Orhan, 2017 ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In primary school a study involving 291 students from Hong Kong found sex differences in the use of SRL strategies, specifically in the strategies of planning, acting on feedback, and self-initiation in academic writing contexts in favor of girls ( Bai et al, 2020 ). In secondary schools, similar results have also been found, for example, research with students from Turkey ( Karademir and Deveci, 2019 ) and other studies with students from China in both face-to-face ( Chen et al, 2023 ) and online learning contexts ( Liu et al, 2021 ) found that self-regulation skills differ significantly as a function of sex in favor of female students. In Higher Education, these differences are also confirmed, for example, a study of 153 undergraduate students of Biological Education in Indonesia showed that female students are more self-regulated, specifically in goal setting, task strategies, time management, and self-evaluation ( Anazifa et al, 2023 ); on the other hand, in a study in 700 undergraduate students of the Faculty of Foreign Languages in Turkey, similar results are revealed showing that female students are more self-regulated in comparison to male students ( Adıgüzel and Orhan, 2017 ).…”
Section: Discussionsupporting
confidence: 78%
“…For example, research on students in Turkey showed that self-regulation skills did not differ significantly as a function of grade (Karademir and Deveci, 2019). The same was concluded by a study that analyzed differences in 1,113 students in grades 11 and 12 of a public secondary school in China (Chen et al, 2023). On the other hand, an interesting result from a cross-sectional study of 1.260 Shanghai secondary school students in China (grades 10-12) analyzed whether the SRL level of these students varied across grades, although, these differences were not significant, still, the authors conclude from their findings of descriptive analyses that, in general, students' SRL decreased as they got older (Guo, 2020); based on the analyses of mean differences by grade in the use of selfregulation strategies, since it was evidenced that 10th and 11th-grade students reported higher means compared to 12th-grade students in the strategies of rehearsal, elaboration, organization, metacognitive strategies, and intrinsic motivation.…”
Section: Discussion Of Rq1 Differences In the Levels Of Srl According...mentioning
confidence: 77%
“…In online environments, students who are equipped with self-regulatory skills have better chances to achieve their goals, as self-regulated learning can significantly improve students’ capacity to exercise self-control, self-monitor and self-evaluate in virtual classrooms ( Öztürk and Çakıroğlu, 2021 ; Lei and Lin, 2022 ; Saint et al, 2022 ). To be particular, for EFL learners, self-regulated learning has significant advantages in terms of increasing their self-direction and self-management and encourage them to be independent and autonomous when engaged in online activities ( Guo et al, 2021 ; Teng, 2021 ; Chen et al, 2023 ; Shen et al, 2023 ). As long as L2 learning is considered, given that it can facilitate the dynamic personality of students’ interactions, self-regulated learning is often considered to be one of critical learning strategies for blended learning ( Xu et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are studies that used motivational constructs for grouping (Bembenutty, 1999;Meece & Holt, 1993;Rosenzweig & Wigfield, 2017), but some others used both motivational and strategy use constructs (Alexander et al, 1995;Alexander & Murphy, 1998;Pintrich, 1989). While many studies researched group effects on SRL behaviour (Järvelä et al, 2019;Lajoie et al, 2015;Nelson et al, 2015), recently, the interest has shifted toward more learner profiles and changes over time (Chen et al, 2023;Dörrenbächer & Perels, 2016;Greene et al, 2021;Hong et al, 2020;Jang et al, 2017;Shell & Soh, 2013). For example, Shell and Soh (2013) identified five student profiles and studied how the SRL strategies were different among students.…”
Section: Literature Reviewmentioning
confidence: 99%